The Impact of the Syrian Civil War on One Department in an Israeli Hospital - Sagi, Omer I.; Ohana, Nissan; Appel, Richard; Kogan, Leonid (Seminars in Plastic Surgery, 2022)
During the Syrian civil war, Syrian refugees crossed the Israeli border to receive medical treatment. During this time, Galilee Medical Center (GMC) became the main center for multidisciplinary treatment of these war-wounded patients. This retrospective study compares the demographics of local Israeli and refugee Syrian patients, as well as the volume and types of procedures each group received over a 5-year period. From January 2013 to December 2017, 963 unique patients underwent 1,751 procedures in the GMC Plastic Surgery Department. Of these patients, 176 were Syrian—including 42 children—and 787 were Israeli. These groups underwent 393 and 1,358 procedures, respectively, for a procedure-per-patient ratio of 2.23 versus 1.72, respectively. On average, Syrian patients tended to be younger than Israeli patients (23.6 vs. 49.25 years), had longer median hospitalization time (50 vs. 8 days), longer median operative times (102 vs. 85 minutes), and higher incidence of infection with multidrug-resistant bacteria (52.2 vs. 5.8%). Further, Syrian patients had more trauma-related procedures, such as skin grafts, wound debridement, and microsurgery, than Israeli patients. Through this process, GMC's plastic surgery department gained unprecedented exposure to a variety of complex procedures.
Keywords: Syrian war; civil war; plastic surgery; health care service; Galilee Medical Center